From self‐defeating to other defeating: Examining the effects of leader procrastination on follower work outcomes. Issue 2 (26th February 2018) - Legood, Alison; Lee, Allan; Schwarz, Gary; Newman, Alexander
Abstract : This research examines the influence of leader procrastination on employee attitudes and behaviours. While previous studies have typically viewed procrastination as a form of self‐defeating behaviour, this research explores its effects on others in the workplace. In Study 1, using data collected from 290 employees, we demonstrate the discriminant and relative predictive validity of leader procrastination on leadership effectiveness compared with laissez‐faire leadership and directive leadership. In Study 2, based on dyadic data collected in three phases from 250 employees and their 23 supervisors, we found that leader procrastination was associated with follower discretionary behaviour (organizational citizenship behaviour and deviant behaviour). Additionally, job frustration was found to mediate the relationship between leader procrastination and follower outcomes. The quality of the leader–follower relationship, as a boundary condition, was shown to mitigate the detrimental effects of leader procrastination. Together, the findings suggest that leader procrastination is a distinct form of negative leadership behaviour that represents an important source of follower job frustration. Practitioner points: Leader procrastination is different from laissez‐faire and directive leadership and can be detrimental to followers. Job frustration mediates the relationship between leader procrastination and follower discretionary behaviour. Organizations should facilitate high‐quality LMX relationships as a method for mitigating the negative effects of leader procrastination.